Dietary sodium-to-potassium ratio as a risk factor for stroke, cardiovascular disease and all-cause mortality in Japan: the NIPPON DATA80 cohort study. Issue 7 (13th July 2016) - Okayama, Akira; Okuda, Nagako; Miura, Katsuyuki; Okamura, Tomonori; Hayakawa, Takehito; Akasaka, Hiroshi; Ohnishi, Hirofumi; Saitoh, Shigeyuki; Arai, Yusuke; Kiyohara, Yutaka; Takashima, Naoyuki; Yoshita, Katsushi; et al.
Abstract : Objectives: To evaluate the impact of dietary sodium and potassium (Na–K) ratio on mortality from total and subtypes of stroke, cardiovascular disease (CVD) and all causes, using 24-year follow-up data of a representative sample of the Japanese population. Setting: Prospective cohort study. Participants: In the 1980 National Cardiovascular Survey, participants were followed for 24 years (NIPPON DATA80, National Integrated Project for Prospective Observation of Non-communicable Disease And its Trends in the Aged). Men and women aged 30–79 years without hypertensive treatment, history of stroke or acute myocardial infarction (n=8283) were divided into quintiles according to dietary Na–K ratio assessed by a 3-day weighing dietary record at baseline. Age-adjusted and multivariable-adjusted HRs were calculated using the Mantel-Haenszel method and Cox proportional hazards model. Primary outcome measures: Mortality from total and subtypes of stroke, CVD and all causes. Results: A total of 1938 deaths from all causes were observed over 176 926 person-years. Na–K ratio was significantly and non-linearly related to mortality from all stroke (p=0.002), CVD (p=0.005) and total mortality (p=0.001). For stroke subtypes, mortality from haemorrhagic stroke was positively related to Na–K ratio (p=0.024). Similar relationships were observed for men and women. The observed relationships remained significant after adjustment for other risk factors. Quadratic non-linear multivariable-adjusted HRs (95% CI) in the highest quintile versus the lowest quintile of Na–K ratio were 1.42 (1.07 to 1.90) for ischaemic stroke, 1.57 (1.05 to 2.34) for haemorrhagic stroke, 1.43 (1.17 to 1.76) for all stroke, 1.39 (1.20 to 1.61) for CVD and 1.16 (1.06 to 1.27) for all-cause mortality. Conclusions: Dietary Na–K ratio assessed by a 3-day weighing dietary record was a significant risk factor for mortality from haemorrhagic stroke, all stroke, CVD and all causes among a Japanese population.